Sobrecarga de cuidadores familiares de pessoas com transtornos mentais: análise nos serviços de saúde - Eloia, Sara Cordeiro (2015)
The new form of taking care in mental health with emphasis on community service has allowed families to live with mental patients and recognize themselves as their main care providers. This new context should be reference for studies and debates in the academic and social areas to guide decision-making in the caregivers‟ assistance, due to the tasks assigned to this role and the possible overload. The purpose of this study was to analyze the degree of objective and subjective overload felt by family caregivers of patients treated by the Geral Psychosocial Care Center (CAPS Geral), Psychosocial Care Center Alcohol and Drugs (CAPS AD) and in an Inpatient Psychiatric Unit in a General Hospital (UIPHG) in the city of Sobral, Ceará, discussing the statistically significant differences. Adopted the quantitative methodology, cross-sectional, exploratory and descriptive, which included 385 caregivers, 216 of the CAPS Geral, 86 from CAPS AD and 83 caregivers of UIPHG. A structured interview was conducted out by applying a sociodemographic questionnaire and the Family Burden Interview Schedule (FBIS–BR). It was used EXCEL and SPSS software for organizing and analyzing statistical data. The level of significance was 5%. The results showed that the three groups, the activities held more frequently by family caregivers related to the daily tasks of patient care and producing more disturbing were the supervision of problematic behaviors of these patients. The degree of objective global burden was higher in the group of caregivers from the UIPHG. In the analysis of objective subscales, this group showed higher overload concerning the supervision of difficult behaviors and the impact on daily routines. However, the group of caregivers of CAPS Geral presented more objective overload concerning care in everyday life. There was no difference between groups of caregivers regarding the subjective global overload. However, when analyzing the subscales individually, the group in UIPHG felt more bothered by observing the problematic behaviors and more concerned about the future and the type of aid and medical treatment of the patient. Variables such as sex and age were associated with overload. These results indicate that professionals must rethink strategies of support and intervention for the appropriate assistance the needs of families in each mental health service.